Tau protein plays a role in the mechanism of cognitive disorders induced by anesthetic drugs - Chen, Zheping; Wang, Shenghan; Meng, Zhaoqian; Ye, Yuyang; Shan, Guoliang; Wang, Xinyue; Zhao, Xin; Jin, Yanwu (Frontiers in Neuroscience, 2023)
Cognitive disorders are mental health disorders that can affect cognitive ability. Surgery and anesthesia have been proposed to increase the incidence of cognitive dysfunction, including declines in memory, learning, attention and executive function. Tau protein is a microtubule-associated protein located in the axons of neurons and is important for microtubule assembly and stability; its biological function is mainly regulated by phosphorylation. Phosphorylated tau protein has been associated with cognitive dysfunction mediated by disrupting the stability of the microtubule structure. There is an increasing consensus that anesthetic drugs can cause cognitive impairment. Herein, we reviewed the latest literature and compared the relationship between tau protein and cognitive impairment caused by different anesthetics. Our results substantiated that tau protein phosphorylation is essential in cognitive dysfunction caused by anesthetic drugs, and the possible mechanism can be summarized as “anesthetic drugs-kinase/phosphatase-p-Tau-cognitive impairment”.